Antimicrobial Susceptibility Patterns of Aerobic Bacterial Species of Wound Infections in Baquba General Teaching Hospital-Diyala - Al-Azawi, Zianab H (Diyala Journal of Medicine, 2019)
Background: Wound infections are the most common hospital-acquired infections and are an important cause of death. Objective: This study was carried out to determine the isolation rate of different aerobic bacterial pathogens from wound infections of hospitalized patients, and their antimicrobial susceptibility patterns in Baquba General Hospital in Diyala province. Materials and methods: This prospective study was conducted for six months from November 2010 to April 2011 in surgical units of Baqubah General Teaching Hospital. Wound swabs were obtained from hospitalized patients who developed wound infections and processed in microbiology laboratory. Pus swab from each patient was collected aseptically, and inoculated on culture media. Isolates were characterized, and identified, and Antibiotic susceptibility patterns were determined using the Kirby-Bauer diffusion method. Results: of total (100) swabs studied, (88%) were culture positive and (12%) were negative. Staphylococcus aureus isolates were 34(38.6%), followed by Escherichia coli and Pseudomonas aeruginosa were 28(31.8%), 24(27.3%) respectively. Both of Klebsiella pneumonia and Proteus vulgaris were 14(15.9), Streptococcus pneumonia and Streptococcus pyogenes were 12(13.6%), 4(4.5) respectively. The antibiotics susceptibility pattern for Ciprofloxacin and Gentamycin were (78.5%), (69.2%) respectively, followed by Streptomycin (43.1%) , Ampicillin (20%) and Amoxicillin (12.3%). Conclusion: S. aureus and E. coli were the most common isolates from wound infections. Ciprofloxacin and Gentamycin were the most effective antibiotics.